Computer-Assisted and Traditional Psychological Assessment of Elementary-School-Aged Children. - Katz, Larry; Dalby, J. Thomas (Contemporary Educational Psychology, 1981)
Computer-assisted psychological assessment was evaluated as a possible alternative to traditional assessment methods. Forty gifted children and forty behavior problem children were administered the State Anxiety and FIRO-BC personality inventories. Half from each group were tested using a cathode ray tube computer terminal while the others were given standard written forms of the tests. All children were retested at a mean interval of 1 week using the same procedures. Test–retest correlations were significant for all six FIRO-BC personality scales regardless of assessment method. Time required to administer and score the inventories was significantly reduced by the computer procedure. While the children's initial perceptions of computers were generally favorable, the perceptions of those children who received the computerized tests significantly increased. Measures of mean state anxiety were uniform with all groups showing significant decreases from first to second testing sessions. These findings suggested that interactive computer assessment may provide a viable alternative to traditional assessment methods with children.